Ethanol extract of Imperata Cylindrica leaves inhibits proliferation and migration of HSC-3 cell lines - Moehamad Orliando Roeslan; Gabriella Tasha (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Squamous cell carcinoma (SCC) is classified as the most common type of oral cancer up to 90% of all malignant neoplasm in the oral cavity. Currently, the only treatments for SCC are surgery and/or radiation or chemotherapy, which can cause various side effects. Cogon grass leaves (Imperata cylindrica) have been considered an alternative cancer treatment that may reduce side effects. Imperata cylindrica (I. cylindrica) leaf extract can inhibit cancer cell proliferation and migration by withholding the cell cycle in the gap 1/synthesis (G1/S) and gap 2/mitosis (G2/M) phases. Therefore, the levels of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) is decreased and cancer is not progressing. Purpose: The study aims to determine the effect of I. cylindrica leaf extract on the proliferation and migration of human oral squamous carcinoma-3 (HSC-3) cell lines. Methods: This in vitro experimental study was conducted with nine study groups. The treatment group was divided into seven concentrations—640 ppm, 320 ppm, 160 ppm, 80 ppm, 40 ppm, 20 ppm and 10 ppm. 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium-bromide (MTT) assay and scratch assay were carried out to assess the effect of I. cylindrica leaf extract on HSC-3 cell proliferation and migration. Results: Ethanol extract of I. cylindrica has a significant effect compared to the negative control towards the proliferation and migration of HSC-3 cells. Conclusion: This study shows that I. cylindrica ethanol leaf extract can inhibit proliferation and migration of HSC-3 cells.